Tacit knowledge augmented customer relationship management systems: An empirical investigation - Abdul Basit; Asma Tahir; Mumtaz Muhammad Khan; Muhammad Ijaz Latif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Tacit knowledge (TK) is a core value element important for obtaining a competitive edge for Customer Relationship Management (CRM). CRM is recognized of high value for integrating knowledge in marketing function. The focus on explicit knowledge so far has resulted in neglecting the importance of TK which is embedded in the minds of employees directly interacting with the customers. The Cross Functional Team (CFT) interaction is an important consideration for explicit and TK exploration and intrapolation. This paper aims to tap and process this TK both of customers and employees to incorporate it in strategic marketing decision making. This paper finally proposes a TK Augmented CRM Systems (TKACRMS) model that guides the integration of employees TK in CRM and validates the proposed model with the help of accidences' of Community of Practice (CoP). The study follows the post-positivist approach as philosophy and triangulation as methodology. An extensive review of literature has been conducted in the domain of marketing, relationship marketing, customer relationship management and knowledge management (particularly TK). After revisiting the definitions of TK and the phenomena associated with the dichotomy of TK, a TK augmented CRM model is developed and empirically tested. The CoP's support the basic hypothesis and agree that TK augmented CRM system is better than contemporary CRM's in developing company's marketing strategy. The main difficulty in Knowledge Management (KM) is the difficulty in diffusing and sharing of TK. CFT suggests the way TK can be diffused and shared across the departments within the organization. The involvement of human being is necessary to interpret the knowledge and specially conceptualize the complexity associated with the TK. The study is subject to all usual research limitations that offer supplement to the future research opportunities. The study provides the guidance to marketers, top management, decision makers and practitioners to enhance the effectiveness of Strategic Marketing Decision (SMD) making. Integrating TK in CRM system by first developing a model and then empirically testing it with a view to incorporate customers' TK through employees.
Keywords: 330; customer relationship management; explicit knowledge; tacit knowledge; relationship marketing; pricing strategy; advertising effectiveness; product value; strategic marketing decision (SMD)